Regulation of Sanctions and Supporting Measures for the Enforcement of Laws against Human Trafficking in Indonesia - Dian Ety Mayasari (Technium Social Sciences Journal, 2023)
Law Number 21 of 2007 concerning the Criminal Act of Human Trafficking has been enacted in Indonesia. Nevertheless, the government of this country cannot independently eradicate human trafficking and requires collaboration with other countries, given the organized nature of this criminal act, where one country may function as the sender, and another as the recipient. This paper employs a normative juridical method that prioritizes literature review, emphasizing legal regulations and literature pertaining to the crime of human trafficking. The occurrence of human trafficking is not solely attributed to the weakness in law enforcement but is also influenced by factors such as poverty, patriarchal culture, and economic incentives. Law enforcement in Indonesia cannot operate independently but requires cooperation with other countries, considering Indonesia’s geographically strategic position as both a transit hub and a source of human trafficking. This collaboration is crucial in the processes of apprehension, extradition, and prosecution of individuals involved in human trafficking, making a significant contribution to the efforts to eradicate this crime.